Persepsi Masyarakat Terhadap Kesejahteraan Keluarga di Desa Sagu Sukamulya Kecamatan Kotawaringin Lama Kabupaten Kotawaringin Barat - Sukmaliani, Sukmaliani; Liling Lenlioni; Sundari, Sundari; Kuwing Baboe (FKIP, Universitas Palangka Raya, 2023)
The perception raised in this study is how the community’s perception of family welfare in the village of Sagu Sukamulya, Kotawaringin Lama district, West Kotawaringin Regency. This study aims to determine the community’s perception of family welfare in the village of Sagu sukamulya, Kotawaringin Lama District, West Kotawaringin Regency. The study uses a qualitative method using a approach descriptive, while the data collection, the author uses of method interviews, observations and documentation. As for the data analysis, the authors use data reduction, data presentation, and drawing conclusions. From the results of research that has been done, it can be concluded that the public’s perception of family welfare. The perception of the community that most of the community’s understanding of family welfare is that they know that family welfare is good in general they already know what family welfare is, so the head of the family is trying to improve the quality of family welfare through family members by means of family members continuing their education to college so that family members can become quality human resources. However, there are also family heads who put more emphasis on family members by increasing their income, namely with family members who start working after graduating from high school/vocational equivalent without continuing their education to a higher level. So based on the views and perceptions of the people above that more people from the Sasak (Lombok) tribe are more supportive of the education of their family members compared to the Javanese and Sundanese. However, the results of the research show that even though the community comes from the same tribe, the same island and even the same work. However, the views on family welfare are different due to the patterns and principles of each family’s life. Although education is very influential on the level of family welfare. But what happened was that the people in the village of Sagu Sukamulya even though they were not graduates of a bachelor’s degree, the community was able to survive with a luxurious lifestyle, because there are people who understand that a prosperous family is a family that is satisfied with the life they lead, something that is easy to achieve, enough to be grateful to get blessings in life and follow the lifestyle desired by each family